A Chinese Approach to International Commercial Dispute Resolution: The China International Commercial Court. (8th June 2020) - Sun, Xiangzhuang
Abstract: This article critically reviews the establishment and operation of the China International Commercial Court (CICC) from an insider's perspective. It offers a detailed introduction to a few of the innovative measures of the CICC, including the International Commercial Expert Committee, the 'one-stop' forum for a dispute settlement mechanism integrating litigation, mediation, and arbitration, more convenient litigation procedures, and the use of advanced technology in dispute resolution. More importantly, it candidly discusses the challenges facing the CICC and makes several recommendations for its improvement towards more professionalism and internationalization.